Search for new physics at the LHC and future colliders - Torres, Yohan Mauricio Oviedo (2023)
It is almost a general consensus that the standard model of particle physics is not the final theory that describes the fundamental interactions between elementary particles. This is because different experimental observations convincingly suggest that the standard theory needs to be extended. Problems such as the need for a candidate for dark matter, the neutrino mass, hierarchy, matter-antimatter asymmetry, among others, point in a very clear direction: experimental searches for signs of physics beyond the standard model in experiments of low and high energies are necessarily urgent. Within the types of high-energy experiments, particle colliders certainly play a fundamental role in this task, since they are machines that can accelerate particles to speeds close to the speed of light and, consequently, are capable of generating very high-energy collisions, enough energy to, for example, produce new particles that are not in the particle spectrum of standard model. Motivated by these open problems and by the enormous potential of particle colliders to test theories beyond the standard model, in this thesis we will approach the study of a new Z' boson from two different perspectives. In the first part of this thesis we will have a detailed study of the standard model that will serve as a basis for presenting the extensions of the standard model that we are going to use. In the second part, we will use data from the ATLAS collaboration to constrain the mass of a new Z' boson using the current LHC configuration for 3-3-1 with right-handed neutrinos and 3-3-1 with heavy neutral leptons models. Once these limits are found, we are going to extrapolate them to the expected updates of high luminosity and high energy of the LHC known as HL-LHC and HE-LHC, respectively, as well as the Future Circular Collider (FCC) projected to work after the LHC. For the third part of this thesis, we will carry out a sensitivity study in the Compact Linear Collider (CLIC) experiment, in which we will obtain the luminosity that the experiment needs to detect a new Z' boson of the 331RHN, 331LHN and Z' leptophilic models. To do this, we will compare a large number of signal and background events to find the best kinematic cuts in which we can see a Z' signal with 95% C.L. or the discovery of a Z' with 5u statistical significance.